Islam and Traditions of The Bugis Pagatan Coastal Community - Jamalie, Zulfa; Wibowo, Fasih (el Harakah: Jurnal Budaya Islam, 2023)
This study concerned the relationship between Islam and traditions commonly practiced by the Bugis Pagatan coastal community. The purpose is to sociologically describe religious life and understand various rites due to a mixture of Islam and traditions. It is a descriptive qualitative, and empirical research that combines sociological, anthropological, and historical approaches to analyze the religious life of the Bugis Pagatan community. The results showed that there are three major traditions in the life of the coastal community, namely religious traditions as part of teaching values (mabbarasanji, massukkiri, mappanrelebbe), rites (mappandretasi'), and life cycle (mappabotting, madutta, mapacci, mappenretojang). Each form of tradition contains religious and cultural symbols as well as deep best values. Religious values found covered devotion, sincerity, and patience, to obtain safety and the blessings of life. Meanwhile, cultural and social values were in the form of honesty, openness, strength, chastity, and honor, to maintenance of harmony and togetherness. Thus, the interaction between Islam and local traditions runs in harmony and mutually reinforces. Islamic acculturation is accepted with the implementation of culture and directed to support spreading the religion. This research recommends the importance of maintaining a harmonious relationship between Islam and culture to prevent conflicts. Penelitian ini mengkaji hubungan antara Islam dan tradisi yang biasa dilakukan oleh masyarakat pesisir Bugis Pagatan. Tujuannya untuk mendeskripsikan secara sosiologis kehidupan beragama dan memahami berbagai ritus akibat percampuran antara Islam dan tradisi. Penelitian ini merupakan penelitian deskriptif kualitatif dan empiris yang memadukan pendekatan sosiologis, antropologis, dan historis untuk menganalisis kehidupan keagamaan masyarakat Bugis Pagatan. Hasil penelitian menunjukkan bahwa terdapat tiga tradisi besar dalam kehidupan masyarakat pesisir Bugis Pagatan, yaitu tradisi keagamaan sebagai bagian dari ajaran nilai (mabbarasanji, massukkiri, mappanrelebbe), ritus (mappandretasi'), dan daur hidup (mappabotting, madutta, mapacci, mappenretojang). Setiap bentuk tradisi mengandung simbol-simbol agama dan budaya serta nilai-nilai terbaik yang mendalam. Nilai religius berupa ketaqwaan, keikhlasan, dan kesabaran, untuk memperoleh keselamatan dan keberkahan hidup. Sedangkan nilai budaya dan sosial berupa kejujuran, keterbukaan, kekuatan, kesucian, dan kehormatan, untuk terpeliharanya kerukunan dan kebersamaan. Kesimpulan, interaksi antara Islam dan tradisi lokal berjalan harmonis dan saling menguatkan. Akulturasi Islam diterima dengan implementasi budaya dan diarahkan untuk mendukung proses penyebaran agama. Penelitian ini merekomendasikan pentingnya menjaga hubungan yang harmonis antara Islam dan budaya untuk mencegah terjadinya konflik.